Review of the Megauchenia Macleay of India (Coleoptera: Nitidulidae: Prometopinae) - Dasgupta, J.; Pal, T.k.; Hegde, V.d. (Zootaxa, 2015)
Three species of Megauchenia Macleay [M. angustata (Erichson, 1843), M. quadricollis (Reitter, 1883) and M. indica (Grouvelle, 1908)] were studied based on a collection from India. The genus and the species are re-described. A key to the species of Megauchenia from India is appended.